In Vitro Multiplication of Nepenthes mirabilis Lour (Druce) with Variations Concentration of Sucrose and BAP (Biosaintifika: Journal of Biology & Biology Education, 2022)
Nepenthes mirabilis (Lour) Druce is a rare ornamental plant and has high economic value so it needs to be preserved. This study aimed to analyze  effect of sucrose and BAP concentrations and their optimal interactions in the in vitro multiplication of Nepenthes mirabilis. Explants in the form of in vitro plantlets from Laboratory of Plant Tissue Culture, Department of Biology, Semarang State University. The treatment was carried out by adding sucrose and BAP to murashige skoog (MS) media with various concentrations. The treatments were arranged in two factor completely randomized design with four replications. Plantlets were planted in the treatment medium for 10 weeks, then every week the growth of shoots and leaves of N. mirabilis was observed. The data were analyzed by two-way analysis of variance and Duncan's test. The results showed that  concentration of sucrose, BAP, and their interactions affected the growth of explants. Plantlets grown on media with sucrose concentration 20 g/l produced the highest number of shoots, media with concentrations BAP 3 and 2 ppm produced the highest number of shoots and number of leaves. Medium ½ MS with varying concentrations of sucrose 20 g/l with 3 ppm BAP and sucrose 20 g/l  with 2 ppm BAP resulted in the highest growth in the number of shoots and number of leaves. The composition of this medium can be used for the multiplication of  N. mirabilis.